Influences Of Neodymium Magnet Configurations On The Stiffness Of A Vibration Based Energy Harvesting Device - A. Ghani, Hilmiah (2016)
Energy harvesting from ambient sources has been a very familiar concept in recent years. In vibration based energy harvesting, resonant linear generators have been the most commonly adopted solution in the harvesting devices. However, several challenges appear when dealing with a linear resonant generator. Among the challenges are the effective power harvested by a linear generator is proportional to the cube of excitation frequency and the power is maximising for a narrow frequency bandwidth only. In this research, ocean wave motion vibration is selected as one of the low frequency sources and its frequency content is investigated. The frequency content is investigated by placing a shock and vibration recorder (MSR) at on-shore, near-shore and offshore at the east coast of Peninsular Malaysia. The measurement shows that the ocean motion vibration is distributed in the low frequency region. Thus, a device that can operate optimally with the low frequency-low amplitude input and has the ability to overcome the narrow frequency bandwidth is invented. Several magnet configurations are suggested to investigate the influences on the stiffness to the proposed design. In one proposed design, the stiffness behaviour of the system is studied by having two single magnets with similar poles (repulsive) and opposite poles (attractive) is placed oppositely. In the second proposed design considered, an oscillating single magnet is placed opposite to the double stationary magnets either attractive or repulsive modes. Another setting is obtained by having an oscillating magnet configured with the repulsive and attractive mode stationary magnets simultaneously. The stiffness of the configurations is related to the degree of non-linearity system. The non-linearity of the system can be adjusted by varying the magnets gap. The non-linear restoring force shows the influences of the linear stiffness and the non-linear stiffness of the system. In this thesis, the analytical solutions to estimate the characteristic behaviour of the magnet configurations are also studied. These proposed designs are then investigated with two main measurements. The quasi-static measurement is conducted to investigate the system stiffness and the dynamic measurement is conducted to investigate the characteristic of the response over a frequency range. It was found that the device is able to increase the frequency as well as amplifying the amplitude of the response. The result also shows that the effective configuration can be made by having the double stationary magnets compared to the single stationary magnet configuration.